Tests of the DMA/GSFC Geopotential Models over Australia - Kirby, Jonathan; Featherstone, Will; Kearsley, A. (International Association of Geodesy, 1998)
The EGM series of geopotential models have been compared with terrestrial free-air gravity anomalies, GPS-levelling data, and an existing gravimetric geoid model in the Australian region. While no significant amounts of new gravity data were included in these geopotential models, a small overall improvement upon OSU91A, JGM3-OSU91A, and GFZ95A was observed.